Shallow active layer temperature and DC resistivity of a rock glacier in the Argentera Massif, Maritime Alps, Italy - RIBOLINI, ADRIANO; FABRE D. (Zeitschrift für Geomorphologie, Supplementary Issues, 2007)
A monitoring of shallow active layer temperature and DC resistivity soundings were performed in the Portette rock glacier, in a region which is considered the southern boundary of permafrost existence in the European Alps. The aim of the work is to recognize the most important seasonal processes that condition the existence or thaw of the permafrost. A one-dimensional geo-electrical survey was adopted to define the permafrost thickness. The active layer temperature was monitored hourly for four years using a digital data logger and a thermistor placed at 20 cm depth. The active layer temperature of three other rock glaciers in the surrounding area was monitored at the same depth and using the same instrumentation. The observed resistivities exceeding 100 k Omega m have been interpreted as permafrost affected layers, in accordance with other active rock glaciers in the Southwestern Alps. The thickness of the permafrost layer exceeds tens of metres both in the upper and middle part of the Portette rock glacier. The thermal behaviour of the active layer is strongly characterized by the occurrence of non-conductive and seasonal heat transfer processes, i.e. release of latent heat during phase change, snow melt infiltration and evidence of air circulation. Thermal events associated with these processes were synchronously registered in the shallow active layers of the other three rock glaciers, evidencing a common thermal behaviour of the Argentera rock glacier during the monitoring period. The ground-air temperature coupling/decoupling indicates that the thickness and establishment of snow cover strongly regulates the occurrence and intensity of these seasonal processes. Delayed and thin snow cover in autumn represents a forcing factor for permafrost maintenance/aggradation because it allows i) a strong cold penetration into the ground, ii) a lack/reduction of the Zero Curtain effect and iii) a downward cold and dense air funnelling. The comparison of the results with regional climatic data indicates that in the ...